2014
DOI: 10.5507/fot.2014.010
|View full text |Cite
|
Sign up to set email alerts
|

Desertifilum fontinale sp. nov. (Oscillatoriales, Cyanobacteria) from a warm spring in East Africa, based on conventional and molecular studies.

Abstract: Abstract:Desertifilum is a filamentous cyanobacterium of crusts and biofilms, recently described from the extreme hot and dry Thar Desert in north-western India. A new species was isolated from a warm spring near Lake Bogoria, Kenya and was characterised by light and electron microscopy and phylogenetically using the 16S rRNA gene, beta and alpha subunits including intergenic spacer (cpcBA-IGS) and 16S-23S internal transcribed spacer (ITS). The aquatic habitat of the new material from Kenya revealed a wider di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…Reporting size dimensions as a mean ± SD without giving ranges (Dadheech et al. , Cai et al. , Sinetova et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reporting size dimensions as a mean ± SD without giving ranges (Dadheech et al. , Cai et al. , Sinetova et al.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological characteristics for six sequenced strains of Desertifilum apart from the Mexican strain were compiled from the publications in which they were described or treated (Dadheech et al. , , Bravakos et al. , Cai et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The polyphasic taxonomy applied to the strains of this study revealed taxa known to be part of bloom-forming communities ( Sphaerospermopsis and Nodularia), rock-dwelling communities ( Scytonema and Tolypothrix ), and hot spring cyanobacteria mats ( Desertifilum and Gloeotrichia ) (Dadheech et al, 2014; Mazur-Marzec et al, 2015; Gkelis et al, 2017; Joanna and Andrzej, 2018). Our results revealed the presence of taxa not previously described from Greek habitats (Gkelis et al, 2016), such as Allinostoc (Saraf et al, 2018) and Oculatella (Osorio-Santos et al, 2014) and taxa previously described only from the tropical zone like Komarekiella and Kovacikia (Miscoe et al, 2016; Hentschke et al, 2017).…”
Section: Discussionmentioning
confidence: 94%